Menumbuhkan Jiwa Kewirausahaan Sejak Dini Kelas III Pada SD Negeri 18 Kota Bengkulu - Ferdian Fachrie Hero Putra; Aji Sudarsono (Universitas Dehasen Bengkulu, 2024)
The introduction or application of the entrepreneurial spirit of students from an early age is very important to create creative and innovative individuals, at SD Negeri 18 Bengkulu city, the application of the entrepreneurial spirit has been applied in a school environment supported by the family environment. To find out the entrepreneurial spirit of students, researchers are interested in fostering the entrepreneurial spirit of SD Negeri 18 Bengkulu city students. The purpose of this community service activity is to foster the entrepreneurial spirit of students of SD Negeri 18 Bengkulu city. The methodology used in this activity is by conducting observations, interviews to obtain information about existing problems and to determine the object to be addressed, then this activity is carried out by providing understanding and training in fostering the entrepreneurial spirit at an early age. Participants in this activity are students of SD Negeri 18 Bengkulu city, teachers, principals and parents of students. From the results of the evaluation of the activity that this activity succeeded in having a positive impact on students of SD Negeri 18 Bengkulu City from the results of questions and answers and from observing the results of training conducted by students in making a work that has selling value.